Pengaruh Konsentrasi Pemutih Terhadap Intensitas Cahaya dalam Lampu SUHEP Alternatif Penerangan - Sri Endang Wahyuni; Puji Suharmanto; Fita Widiyatun (Universitas Indraprasta PGRI Jakarta, 2020)
SUHEP lamps are designed as an alternative lighting during the day for a closed room. The research method used in the form of an experiment in the difference in the concentration of bleach in SUHEP lamps to produce lighting that meets the standards of 100 - 250 Lux. Tool for measuring the value of light intensity is a luxmeter and the resistance value at 5 mm and 12 mm LDR using an avometer. The relationship of light intensity with resistance is influenced by several factors namely the smaller the size of the LDR is, the greater value of resistance is because the surface area of the light intensity is getting smaller. Another influencing factor is the greater the room temperature value is, the greater the value of the light intensity is. The comparison of the concentration of bleach to water also shows the greater concentration of bleach is, the smaller the intensity of the light is although this is also very sensitively influenced by the weather. Based on the results of the research it is found that each sample of the light intensity of the SUHEP lamp ranges from 172 - 201 lux and the value of the resistance produced by 5 mm LDR ranges from 800 - 1200 Ohm while by 12 mm LDR, resistance value ranges from 600 - 800 Ohm. From the research results it can be concluded that the ideal concentration between bleach and water in the SUHEP Lamp is 5%: 95% for 201 lux.